Maturity‐onset diabetes of the young type 5, presenting as diabetic ketoacidosis with alkalemia: A report of a case. Issue 5 (10th January 2022) - Hayakawa‐Iwamoto, Akiko; Aotani, Daisuke; Shimizu, Yuki; Kakoi, Shota; Hasegawa, Chie; Itoh, Shunsuke; Fujii, Asami; Takeda, Katsushi; Yagi, Takashi; Koyama, Hiroyuki; Imaeda, Kenro; Nozu, Kandai; et al.
Abstract: A 34‐year‐old man visited our Department of Gastroenterology and Metabolism, Nagoya City University Graduate School of Medical Sciences, Nagoya, Japan, because of dry mouth and weight loss. His plasma glucose level was 32.8 mmol/L and serum levels of ketone bodies were increased, but with metabolic alkalemia. He was also suffering from renal tubular hypomagnesemia and hypokalemia. Abdominal computed tomography showed bilateral renal cysts. These findings were suggestive of maturity‐onset diabetes of the young type 5. Genetic testing showed heterozygous hepatocyte nuclear factor 1 beta gene deletion. In the present case, it seemed reasonable to view hepatocyte nuclear factor 1 beta gene deletion as the common cause of maturity‐onset diabetes of the young type 5‐associated diabetic ketoacidosis and tubular malfunction‐induced hypokalemic alkalosis. This case exemplifies the importance of hepatocyte nuclear factor 1 beta gene abnormality as a potential cause of diabetic ketoacidosis with alkalemia. Abstract : Genetic mutations of hepatocyte nuclear factor 1 beta cause multiple organ disorders, as well as maturity‐onset diabetes of the young type 5, collectively known as the hepatocyte nuclear factor 1 beta syndrome. It can lead to the development of diabetic ketoacidosis with alkalemia.